Backfilling with filtered tailings above an active cave mine: a conceptual study - Clarke, N; Jakubec, J (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
Placing tailings in the subsidence zone of a block or sublevel cave mine during operations would have major benefits, particularly in leaving behind a rehabilitated land surface capable of beneficial use; reducing the area of the subsidence crater and reducing (by at least 50%) the volume of other tailings storage facilities. Surface water flows could be better managed to ameliorate community concerns. In high-rainfall areas underground water management would be simplified; the risks from mud rushes at drawpoints would be reduced and where iron sulphides are present, costs for acid drainage control and treatment would be greatly reduced. With additional oxygen access control measures, tailings backfilling may avoid the need for perpetual treatment of acid drainage after closure. Despite the advantages, the perceived risks have meant that backfilling tailings above an active cave mine has not yet been practiced. The major perceived risk is of a large-scale mud inrush with fatal consequences as at Mufulira in 1970 and Grasberg in 2025. However, filtered tailings, placed so as to prevent surface water accumulation, cannot flow through broken rock and could reduce the risks inherent in an unmanaged subsidence crater. The risks and benefits of progressive backfilling of tailings have been studied in the context of a model mine, based in part on a confidential sublevel cave mining project in tropical South America. The work has involved formal and informal risk reviews, reviews of historical major mud inrush incidents, conceptual engineering analyses and laboratory test work. A 1:100-scale model mine experiment was completed using a block caving withdrawal sequence. The studies to date indicate that backfilling is feasible and risks can be managed. However, experimental work using a new 1:100-scale model mine, structured as a sublevel cave, is continuing. The intention is to obtain quantitative model data on dilution by tailings compared to waste rock fines.
Keywords: backfill; filtered tailings; cave mining; mud inrush